Bentuk-Bentuk Etos Kerja dalam Manajemen Pendidikan dan Pendidikan Islam - Ermida, Ermida; Bustaman, Risman (Jurnal Pustaka Cendekia Pendidikan, 2023)
The work ethic in Islamic education is very important to understand and apply in your duties as an educator. Work ethic includes ethical behavior in work and management of Islamic education. Work ethic is a guide for decision making in Islamic education management. The work ethic in Islamic education includes moral values and Islamic principles that must be applied in the world of work and management of Islamic education. QS. AlBalad: 4 says "and in fact we have created humans in a state of toil". Allah SWT gives promises to believers and those who strive and are serious in carrying out obedience to Allah and defending Allah's religion solely to seek His pleasure. We will show them our path that leads them to happiness and safety in the afterlife. Islamic values have a great influence in shaping a good work ethic, including first, sincerity in working to provide the best educational services for students second, resignation or surrender to Allah to realize that success or failure is the prerogative of Allah SWT third , justice is very important in respecting the rights of all parties involved in the education process: fourth, trustworthiness in managing human resources, budgets and infrastructure properly fifth, kindness in providing the best educational services with full sense of responsibility, love and affection. A good work ethic is very important in education management and Islamic education. A good work ethic can improve the quality of educational services provided by staff, teachers, to students. A good work ethic can also help create a positive work environment, increase motivation and performance.